Crosstalk of BMP-4 and RA signaling pathways on Pomc gene regulation in corticotrophs - Nieto, Leandro Eduardo (2019)
Retinoic acid (RA), an active metabolite of Vitamin A, and bone morphogenetic protein 4 (BMP-4) pathways control the transcription of pro-opiomelanocortin (Pomc), the precursor of ACTH. We describe a novel mechanism by which RA and BMP-4 act together in the context of pituitary corticotroph tumoral cells to regulate Pomc transcription. BMP-4 and RA exert a potentiated inhibition on Pomc gene expression. This potentiation of the inhibitory action on Pomc transcription was blocked by the inhibitory SMADs of the BMP-4 pathway (SMAD6 and SMAD7), a negative regulator of BMP-4 signaling (TOB1) and a blocker of RA pathway (COUP-TFI). AtT-20 corticotrophinoma cells express RA receptors (RARB, RXRA and RXRG) which associate with factors of BMP-4 (SMAD4 and SMAD1) signaling cascade in transcriptional complexes that block Pomc transcription. COUP-TFI and TOB1 disrupt these complexes. Deletions and mutations of the Pomc promoter and a specific DNA-binding assay show that the complexes bind to the RARE site in the Pomc promoter. The enhanced inhibitory interaction between RA and BMP-4 pathways occurs also in another relevant corticotroph gene promoter, the corticotropin-releasing hormone receptor 1 (Crh-r1). The understanding of the molecules that participate in the control of corticotroph gene expression contribute to define more precise targets for the treatment of corticotrophinomas.